Distúrbios osteomusculares e qualidade de vida em cirurgiões dentistas - Marquesi, Camila [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The World Health Organization (WHO) defined quality of life as individual's perception of their position in life in the context of culture and value systems in which they live, and in relation to their goals, expectations, standards and concerns . The search for quality of life is of paramount importance in work, play a key period of time in human life. However, currently the man is exposed to constant stressful situations arising from work activities favoring the manifestation of various diseases, called occupational diseases. Among these diseases, musculoskeletal work-related disorders (MSDs) are in evidence and Dentistry is a vulnerable profession to these diseases due to working conditions. In this study we evaluated the presence of musculoskeletal disorders, pain symptoms between dentists and the relationship to quality of life. It is a transversal study, analytical and descriptive quantitative approach, the participants were the dentists private sector four small municipalities in the central region of São Paulo, the research instruments were a partner questionnaire -demográfico, Nordic questionnaire musculoskeletal systems and the WHOQOL - Bref. The data were stored and processed, using the BioEstat software version 5.3 and EpiInfo 7. It was found that dentistry there is a predominance of painful symptoms among females (60.4%), the region with the highest reporting pain was the neck and cervical spine (49.2%) compared professionals in pain and without pain, the pain presented with on average a lower score, beyond the physical domain (p = 0.0112), self-assessment of quality of life (p = 0.0061) and the total sum of all domains (p = 0.0438) have statistically significant difference in the two groups. It can be concluded in this study that there is a predominance of painful symptoms among females, whichever...

A Organização Mundial de Saúde (OMS), definiu qualidade de vida como: percepção do indivíduo de sua posição na vida, no contexto da cultura e sistemas de valores nos quais vive, e em relação aos seus objetivos, expectativas, padrões e preocupações. A busca pela qualidade de vida é de suma importância no trabalho, por ocupar um espaço de tempo determinante na vida do ser humano. No entanto, atualmente o homem está exposto a constantes situações estressantes decorrentes das atividades laborais favorecendo a manifestação de diversas patologias, chamadas de doenças ocupacionais. Dentre essas doenças, os distúrbios osteomusculares relacionado ao trabalho (DORT) estão em evidência e a odontologia é uma profissão vulnerável a essas doenças, devido as condições de trabalho. Neste estudo o objetivo foi avaliar a presença de distúrbios osteomusculares, sintomatologia dolorosa entre cirurgiões- dentistas e a relação com a qualidade de vida. Trata-se de um estudo transversal, analítico e descritivo de caráter quantitativo, os participantes da pesquisa foram os cirurgiões dentistas do setor privado de quatro municípios de pequeno porte da região central do estado de São Paulo, os instrumentos de pesquisa foram: um questionário sócio-demográfico, questionário nórdico de sistemas osteomusculares e o Whoqol - Bref. Os dados foram armazenados e processados, empregando-se os softwares BioEstat versão 5.3 e EpiInfo 7. Verificou-se que na odontologia há um predomínio da sintomatologia dolorosa entre o gênero feminino (60,4%), a região com maior relato de dor foi a do pescoço e coluna cervical (49,2%), em comparação dos profissionais com dores e sem dores, os com dores apresentaram na média...
Keywords: Qualidade de vida; Engenharia humana; Doenças profissionais; Transtornos traumáticos cumulativos; Odontólogos; Quality of life